Prognostic Utility of the New Definition of Difficult-to-Treat Resistance Among Patients With Gram-Negative Bloodstream Infections. (12th December 2019) - Giannella, Maddalena; Bussini, Linda; Pascale, Renato; Bartoletti, Michele; Malagrinò, Matteo; Pancaldi, Livia; Toschi, Alice; Ferraro, Giuseppe; Marconi, Lorenzo; Ambretti, Simone; Lewis, Russell; Viale, Pierluigi
Abstract: Background: To compare the prognostic utility of the new definition of difficult-to-treat resistance (DTR) vs established definitions in a cohort of patients with Gram-negative bloodstream infections (GNBSIs). Methods: This was a retrospective single-center study of adult patients with monomicrobial GNBSI, hospitalized from 2013 to 2016. DTR was defined as isolate demonstrating intermediate or resistant phenotype to all reported agents in the carbapenem, beta-lactam, and fluoroquinolone classes. Carbapenem resistance (CR) was defined according to 2015 Centers for Disease Control and Prevention criteria. Each isolate was further classified according to the Magiorakos et al. criteria as non-multidrug-resistant (non-MDR), MDR, extensively drug-resistant (XDR), or pan-drug-resistant (PDR). The primary outcome was all-cause 30-day mortality. Results: Overall, 1576 patients were analyzed. Enterobacteriaceae accounted for 88.7% of BSIs, with Escherichia coli (n = 941) and Klebsiella pneumoniae (n = 326) being the most common pathogens. Pseudomonas aeruginosa was the most common nonfermentative bacteria (n = 130, 8.2%). Overall, 11% of strains were defined as DTR and 13% as CR. Episodes were further classified as non-MDR (68.8%), MDR (21.9%), XDR (8.8%), and PDR (0.4%). The prevalence rates of DTR, CR, and XDR were similar among Enterobacteriaceae and Acinetobacter baumannii, whereas they differed in P. aeruginosa . All the analyzed resistance definitions significantly improved prediction of 30-day mortality when introduced into a baseline multivariate model, to a similar degree: 9%, 10%, and 11% for DTR, Magiorakos, and CR definitions, respectively. Conclusions: DTR seems a promising tool to identify challenging GNBSIs, mainly those due to P. aeruginosa . With the availability of new agents for CR infections, further multicenter assessments of DTR are needed.